(untitled) (Eurasian Medical Research Periodical, 2023)
The article presents a clinical case of malignant retroperitoneal schwannoma, which was a diagnostic finding. The clinical picture of the disease was dominated by pain in the lower abdomen and lower back, frequent urination. After a diagnostic examination and preliminary preparation, the patient was operated on in a hospital at the oncogynecology department of the Tashkent City branch of the Republican Specialized Scientific and Practical Medical Center of Oncology and Radiology with a preliminary diagnosis of an ovarian tumor. Interrooperatively, a tumor of the retroperitoneal space with lesions of the obturator nerve was revealed. Subsequently, immunohistochemical (IHC) analysis clarified the organ belonging and the histological type of the tumor, which turned out to be a malignant schwannoma of the retroperitoneal space. These data may help in the management of patients with this pathology and improve the diagnosis of patients with pelvic tumors